Addressing Negative Externalities of Urban Development: Toward a More Sustainable Approach - Christopher R. Correia; Mark Roseland (Urban Science, 2022)
The sheer size, growth, and complexity of cities worldwide are creating an ever-increasing burden of negative externalities on society and the environment. This systematic review aims to illuminate the broad range of negative urban development externalities and to analyze them in way that sharpens our ability to perceive, anticipate, and manage them. After finding that negative urban development externalities are more complex and diverse than has been previously articulated in the literature, the paper categorizes a representative sample by type (social, environmental, and economic) and identifies three modes of impact (visibility, emergence, and distribution) that make them extremely challenging to anticipate and mitigate. The most problematic negative externalities are social or environmental, with low visibility, cumulative patterns of emergence, and effects that extend beyond regulating jurisdictions. The analysis then draws on welfare economics to strengthen the case for the proactive management of these negative externalities and analyzes the competencies and capacities of local governments to strategically intervene in order to more effectively achieve sustainable development.